Exploring the standardization of human nasal antibody measurements - Xuanxuan Zhang; Yulong Fu; Si Chen; Guanxing Liu; Ying Wang; Qian He; Qian Wang; Na Li; Zhongfang Wang; Ling Chen; Junzhi Wang; Zhenglun Liang; et al. (Emerging Microbes and Infections)
Mucosal immunity is crucial for preventing the infection and transmission of respiratory viruses. Nasal antibody is inversely correlated with a lower risk of infection with respiratory viruses. However, the current reference standard for nasal antibody assessment is serum-based, mainly consisting of monomeric IgG and IgA. The applicability of serum-derived standards for assessing nasal antibodies, consisting mostly of dimeric or polymeric secretory IgA (sIgA), remains unvalidated. Herein, we first proved that the sera-derived standard was not applicable for assessing nasal antibodies. Using a non-homologous standard as a calibrator introduced systematic error up to 10 times, which did not benefit the understanding of mucosal antibody response. Therefore, we attempted to develop two candidate standards (CS1, CS2) using nasal mucosal lining fluids (NMLFs) collected from SARS-CoV-2 Omicron convalescents or intranasal vaccine recipients, and CS3 using a sIgA monoclonal antibody. CS2 exhibited broad-spectrum binding activity against 12 SARS-CoV-2 strains, including all tested Omicron subvariants. A collaborative study conducted by seven laboratories demonstrated that CS2 improved the harmonization of inter-laboratory variability (pre-standardization geometric coefficients of variance, 14–314%; post-standardization, 3–35%). Using CS2 ensured an accurate assessment of nasal antibodies. Thus, CS2 was established as a national standard for evaluating nasal SARS-CoV-2-specific antibodies (Lot: 300052-202401, 1000 U/mL). Our work provides a benchmark for evaluating mucosal vaccines for SARS-CoV-2 and inspires new avenues for developing new reference standards for other mucosal vaccines.